The Development of Productive Economy Cluster through Siparti 3-S and Triple Helix in Kabupaten Lumajang, Indonesia - Wulandari, Dwi; Witjaksono, Mit; Soseco, Thomas; Narmaditya, Bagus Shandy (International Journal of Economics and Financial Issues, 2017)
The low rate of productivity in agriculture sector potentially reduce its ability to provide welfare to farmers. Furthermore, it will preserve vicious circle of poverty. Thus, it is important to produce superior products of one region. Superior products, which made by local resources, potentially affect the community in a village. This research aimed to identify local resources and potential relationship that may be build. This research used mix methods, which is combine qualitative and quantitative methods, by using sequential exploratory strategy. This research is conducted in Kabupaten Lumajang, Indonesia. Some problems raised in our study area. They are asymmetric information, income disparity, and weak farming management. All of them persist from a long time ago, without no strong desire to overcome them. We propose two models to overcome the problem. The first is Siparti 3-S. Siparti 3-S involve synergy of the three basic resources: human resources, natural resources, and social and cultural resources. The second models are Synergy Government-University-Industry into Triple Helix. It is important to work together with the university, local government, and local industry. Thus, by implement those models, citizens are able to produce superior products so that they can raise their welfare. Keywords: Kabupaten Lumajang, Siparti 3-S, Triple Helix. JEL Classifications: G15, O112, O18